Biological Importance, Therapeutic Benefits, and Analytical Aspects of Active Flavonoidal Compounds ‘Corylin’ from Psoralea corylifolia in the Field of Medicine - Patel, Dinesh K. (Infectious Disorders - Drug Targets, 2023)
Background: Flavonoidal class phytochemicals are the best examples of secondary metabolite found in different natural sources, including ‘fruits, grains, vegetables, broccoli, tea, berries, wine, strawberries, apples, grapes, lettuce, and citrus fruit. Natural products are a rich source of flavonoidal compounds present in our diet source. Objective: Flavonoidal class chemicals can be subcategorized into chalcones, isoflavone, flavonols, catechin, flavones, flavanones, and anthocyanidin with respect to their basic chemical structures. Psoralea corylifolia L. belongs to the family Fabaceae and is an herbal medicine used in traditional Chinese Medicine for the treatment of inflammatory disorders, bacterial infections, and cancerous disorders. Methods: In the present work, scientific data have been collected from different databases and analyzed in order to find the therapeutic potential of corylin in medicine. Different scientific databases such as Google, Scopus, PubMed, Science Direct, etc., have been searched to collect the needed scientific information on corylin. Scientific information on corylin has been collected in the present work in order to know the pharmacological activities and medicinal uses of corylin in the scientific fields. However, analytical techniques data of corylin have also been collected and analyzed for standardization of Psoralea corylifolia and other medicinal plants. Results: Scientific data analysis of research works revealed the medicinal importance of Psoralea corylifolia and its important phytoconstituents corylin in medicine. Scientific data analysis revealed that corylin is a flavonoidal class phytochemical found in the nuts of Psoralea corylifolia L. Biological importance of corylin in bone differentiation, bone growth, and osteoporosis has been proven in this scientific research work. The anti-inflammatory, anti-oxidant, and antitumor activity of corylin has been also described in this medical literature. The biological importance of corylin in hyperlipidemia, insulin resistance, atherosclerosis, hepatocellular carcinoma, and neurodisorders have also been presented in this work. Conclusion: Scientific data analysis revealed the biological importance and therapeutic potential of corylin in the field of medicine.
Keywords: therapeutic benefit